Learning and Instruction: Social-Cognitive Perspectives - Carugati, Felice; Perret-Clermont, Anne-Nelly (My University, 2015)
In this article, we try to expand the lenses classically used in social psychology of development, and in particular, in the post-Piagetian tradition, to recent contributions of social and cognitive dynamics in development and learning. Psychological development has to be redefined as involving socially framed, culturally mediated, and interpersonally negotiated processes, and the dynamic relation between the person, others, objects, and instruments that are reconfigured through teaching–learning activities. The units of analysis, besides the traditional focus on the individual and/or isolated cognitive event, also include nowadays peer interaction and partners' roles, dialogical processes, argumentation, and specific institutional features of human practices, as illustrated through experimental social psychology. According to this general framework, learning and thinking appear more clearly as the collaborative result of autonomous minds confronting viewpoints and cultural artifacts (tools, semiotic mediations, tasks, division of roles) and trying to manage differences, feedbacks, and conflicts to pursue their activities. Moving from one activity to another, and from one space to another (pretest, joint activity, posttest), children have to reorganize their understanding, their language, and the organization of their social interactions.
Keywords: Argumentation; Classroom learning; Dialogical processes; Experimental social psychology; Levels of analysis; Mastery goals; Social interaction; Sociocognitive activities; Sociocognitive conflict; Sociocultural approach; Teacher's role